Okoliczności kompozycji hymnu Akatyst ku czci Najświętszej Maryi Panny - Grzywaczewski, Józef (Vox Patrum, 2018)
The author of this article tries to situate the famous Greek Hymn Akathistos in its large context. He presents the Old Testament tradition, especially the Psalms, and the New Testament tradition: Christological hymns and the person of Mary in the Gospel. The Christians of the first centuries used to sing hymns during their meetings of prayer. The old Hellenic tradition in poetry and music could also have influence on the Christian poetry and music, especially on the formal aspect of such compositions. It seems to be obvious that the Akathistos was inspired by the theological considerations on Mary as Christ’s Mother. This hymn is a great praise of Mary as Theotokos; this title was accepted officially in the Church by the Council of Ephesus (431). The exact date of the composition of the hymn is not known; it is only known that this hymn was sung in 626 in Constantinople as thanksgiving to Mary for the expelling of the aggressors (a regiment of the Persian army). The question of authorship of Akathistos is still discussed; most scholars attribute it to Romanos Melodus, but such an opinion is considered as probable. The aim of this article is to introduce the lector into the study on the theology of the Akathistos (Christology and Mariology). Surely, such a study can be precious for the Christian spirituality.